2018
DOI: 10.1111/jtxs.12376
|View full text |Cite
|
Sign up to set email alerts
|

Which variables should be controlled when measuring the granulometry of a chewed bolus? A systematic review

Abstract: The distribution of food particles in a chewed bolus characterizes the food destruction after food oral processing (FOP). Previous reviews report that it could be affected by a lot of parameters as the number of chewing strokes, the dental status, but the conditions for producing reproducible data allowing inter‐studies comparison have not been clearly described yet. This systematic review aims to identify the variables that can affect bolus granulometry determination, and to calculate their relative weights i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 93 publications
(174 reference statements)
2
19
0
1
Order By: Relevance
“…Regarding the evaluation method for the particle analysis on mastication, Â50 is one of the most frequently used methods in this field [28]. Here, Â50 is an excellent method to characterize the particle size distribution with one representative value [29]. On the other hand, it is possible to evaluate two indices, particle homogeneity and size, separately using this method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the evaluation method for the particle analysis on mastication, Â50 is one of the most frequently used methods in this field [28]. Here, Â50 is an excellent method to characterize the particle size distribution with one representative value [29]. On the other hand, it is possible to evaluate two indices, particle homogeneity and size, separately using this method.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported higher retrieve rates using silicone dental impression material as artificial test food [31]. However, Bonnet et al stated that the use of non-edible test material would be debatable, especially in the studies that aim to investigate swallowing threshold [29]. They mentioned synthetic materials, such as dental impression materials, were not supposed to be swallowed but induce nonnutritive mastication that generally depends on voluntary command and is more detached from neuro controls compared with mastication of natural food.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in agreement with previous studies stating that PSD of different chewed foods depends on food type but not on individuals, despite variations in masticatory parameters between subjects (11)(12)(13)15) . It has been previously reported that subjects adapt their mastication behaviour depending on factors such as physical food characteristics, including food texture (13,45) . Moreover, it has been postulated that a precisely determined bolus texture, which seems to depend on both particle size reduction and the creation of a cohesive bolus through lubrication with saliva, has to be achieved before swallowing occurs (11,13,15) .…”
Section: Discussionmentioning
confidence: 99%
“…The validation of these hypotheses could be done by in vivo (in appropriate animal models) or in vitro studies via a fine analysis of kinetics of food disintegration along the gut. From mechanical disintegration of food bolus in the mouth [34], to chemical and enzymatic disintegration of the bolus within the stomach and the duodenum/ileum [30,35] including interaction between folates and lipids (and maybe proteins) present in custard/milk in particular, many strands remain under research about the major food parameters that determine food behaviour during digestion and the related nutritional consequences.…”
Section: Resultsmentioning
confidence: 99%